2017
DOI: 10.1016/j.beproc.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Fast- and slow-exploring pigeons differ in how they use previously learned rules

Abstract: Please cite this article as: Guillette, L.M., Baron, D.M., Sturdy, C.B., Spetch, M.L., Fastand slow-exploring pigeons differ in how they use previously learned rules.Behavioural Processes http://dx.doi.org/10. 1016/j.beproc.2016.07.006 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
0
10
2
Order By: Relevance
“…Personality ( Moretz et al, 2007 ; Martins and Bhat, 2014 ; Roy et al, 2017 ; Roy and Bhat, 2018b ) and spatial cognition ( Arthur and Levin, 2001 ; Spence et al, 2011 ) in zebrafish have been characterized and studied, but there have been no forays into deciphering the relationship between the two aspects of behavior. However, recent studies have been performed in multiple taxa, aimed at distinguishing the underlying correlation between personality and cognition ( Carter et al, 2014 ; Bousquet et al, 2015 ; Guillette et al, 2017 ). Our study examined correlations between personality and spatial learning in wild zebrafish and whether personality traits remain consistent over time and context.…”
Section: Discussionmentioning
confidence: 99%
“…Personality ( Moretz et al, 2007 ; Martins and Bhat, 2014 ; Roy et al, 2017 ; Roy and Bhat, 2018b ) and spatial cognition ( Arthur and Levin, 2001 ; Spence et al, 2011 ) in zebrafish have been characterized and studied, but there have been no forays into deciphering the relationship between the two aspects of behavior. However, recent studies have been performed in multiple taxa, aimed at distinguishing the underlying correlation between personality and cognition ( Carter et al, 2014 ; Bousquet et al, 2015 ; Guillette et al, 2017 ). Our study examined correlations between personality and spatial learning in wild zebrafish and whether personality traits remain consistent over time and context.…”
Section: Discussionmentioning
confidence: 99%
“…Also, recent studies suggest that different personality/cognitive styles might have comparable learning rates but use the learned information quite differently (e.g. 36,37 ). Individual differences were also reported in the degree of attention and accuracy devoted to assess a potential threat 38 .…”
Section: Introductionmentioning
confidence: 99%
“…These findings have served as the basis for many studies where fast explorers are predicted to be routine-like and slow explorers are predicted to be more plastic in their behaviors. Still, studies have found mixed results on the relationship between exploration and behavioral plasticity measured in the context of a change in the value of resources (e.g., reversal learning; Bebus, Small, Jones, Elderbrock, & Schoech, 2016;Guillette, Baron, Sturdy, & Spetch, 2017), abiotic conditions (e.g., temperature; Herborn, Heidinger, Alexander, & Arnold, 2014), or biotic conditions (e.g., predation risk; Quinn, Patrick, Bouwhuis, Wilkin, & Sheldon, 2009). For instance, in Herborn et al (2014) fast explorers were reported to change feeders more frequently in response to temperature changes, while slow explorers in Adriaenssens and Johnsson (2010) were suggested to have increased plasticity as they were observed to have higher activity rate with increased experience.…”
mentioning
confidence: 99%
“…Under the BF hypothesis, we predict slower explorers to be more plastic and change their behavior, that is, stop using the familiar option and switch to the novel option, more quickly than faster explorers. Here, we define behavioral plasticity as defined in Greenberg (2003), where plasticity is a modification in foraging behavior (Rockwell, Gabriel, & Black, 2012). Similar to Verbeek et al (1994), we use the "strength of a foraging habit" as the number of visits to a previously rewarding familiar option to measure behavioral plasticity.…”
mentioning
confidence: 99%